Fungal Community Investigation from Propolis Natural Products: Diversity and Antibacterial Activities Evaluation. (16th April 2022) - Sallemi, Souhir; Lekired, Abdelmalek; Korbi, Nedra; Saadouli, Ilhem; Cherif, Ameur; Zidi, Ines; Klibi, Naouel; Ouzari, Hadda-Imene; Mosbah, Amor
Abstract : Discovering new species and interesting bioactive metabolites from customary sources is becoming progressively laborious. Propolis constitutes the largest diversified reserve of microbial constituents in the beehive. However, fungal communities associated with these environments remain insufficiently established. We present the first detailed investigation of the cultivable fungal community associated with Tunisian propolis, and we evaluate its antibacterial properties against pathogenic bacteria. A total of 80 fungal strains were isolated from propolis samples derived from seven different Tunisian locations. The majority of the isolated fungi were classified as Ascomycota (97.5%), and only 2.5% belonged to Basidiomycota . Our collection was clustered into 15 genera, among which Coniochaeta (36.25%), Aspergillus (15%), Penicillium (13.75%), Cladosporium (10%), Fusarium (7.5%), Didymella (5%), and Alternaria (3.75%) were the most common. Evaluation of the antibacterial activity revealed that 25.6% of the total community showed a broad range of antibacterial activity. Particularly, the Penicillium griseofulvum CC8 strain has manifested the strongest inhibitory effects against all the tested bacteria.